Efek sistem pemrosesan informasi rasional dan intuitif pada pengambilan keputusan kewirausahaan: sebuah tinjauan literatur - Ariel Nian Gani; Muhammad Rofi’i; Ikhsan Maksum (Jurnal Ekonomi Modernisasi, 2019)
The use of rational and intuitive information-processing systems is related to the entrepreneurial decision-making effectiveness. This study aims to comprehensively describe the literature that examines the effects of using rational and intuitive systems on entrepreneurial decision making. Leading literature databases are sought for studies published between 1995 and 2017 that evaluate rational and/or intuitive systems in relation to entrepreneurial decision making. We found ten empirical studies that met our inclusion criteria. There is some evidence from this research that the use of intuitive systems can positively influence entrepreneurial decision making in the early stages of entrepreneurship (e.g, opportunity identification). Other studies report mixed results regarding the impact of using rational and / or intuitive information processing systems for decision making at the next entrepreneurial stage (e.g, Exploitation of opportunities and financial performance). Based on the findings of this review, there are three further research opportunities, namely: (1) researchers must begin to learn about the ability of entrepreneurs to match their cognitive information processing systems with task characteristics; (2) assesses the effectiveness of decision making as the main outcome; and (3) study the construction of entrepreneurial behavior at the individual level in relation to the use of rational and intuitive information processing systems.